2016
DOI: 10.1007/s11270-016-2796-0
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Biochar Amendment on Dimethyl Disulfide Emission and Efficacy Against Soil-Borne Pests

Abstract: Biochar can potentially reduce fumigant emissions in agriculture. Dimethyl disulfide (DMDS) is an effective soil fumigant for controlling soil-borne pests. However, it is important to reduce DMDS emissions because the compound has an unpleasant and easily perceived sulfur odor. This study therefore aimed to determine the effects of two types of biochar amendments on DMDS bioactivity and emission, using bioassay methods and soil columns. The efficacy of DMDS for controlling root-knot nematode and Fusarium spp. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
(34 reference statements)
0
5
2
Order By: Relevance
“…Reported DMDS emission reduction from soil resulting from surface applied biochar (mixed hardwood chips produced at~500 • C) was 53% of maximum DMDS concentration in the air [31]. Reductions of DMDS were observed in this study, especially early in the study, but were not significant likely due to high variability over a longer exposure time, 30 d compared to the reported 1 d in [31].…”
Section: Treatment Effects On Volatile Organic Compoundscontrasting
confidence: 59%
See 1 more Smart Citation
“…Reported DMDS emission reduction from soil resulting from surface applied biochar (mixed hardwood chips produced at~500 • C) was 53% of maximum DMDS concentration in the air [31]. Reductions of DMDS were observed in this study, especially early in the study, but were not significant likely due to high variability over a longer exposure time, 30 d compared to the reported 1 d in [31].…”
Section: Treatment Effects On Volatile Organic Compoundscontrasting
confidence: 59%
“…Reductions of DMDS were observed in this study, especially early in the study, but were not significant likely due to high variability over a longer exposure time, 30 d compared to the reported 1 d in [31]. Pinecone biochar produced at 600 • C was reported to have a 74% removal efficiency of DMTS (4 µg·L −1 ) in aqueous solution after 4 h and reached equilibrium within 6 h [32].…”
Section: Treatment Effects On Volatile Organic Compoundscontrasting
confidence: 47%
“…Further research focusing on feedstock and production temperature is therefore desirable in order to increase our knowledge about the effects of biochar amendments on DMDS degradation in soil. The amount of DMDS that was available to escape to the atmosphere was also reduced after biochar amendments applied to the soil surface, compared with other fumigants, the emission of 1,3‐D was reduced after biochar was applied to the surface 5 cm of soil, owing to the enhanced adsorption of 1,3‐D onto biochar, while the emission of CP was reduced by biochar on account of the accelerated degradation of CP in soil amended with biochar …”
Section: Resultsmentioning
confidence: 99%
“…In our previous studies, we found that amending soil with biochar can reduce the emission of DMDS to the atmosphere . However, the principles of DMDS emission reduction by biochar are not yet clear.…”
Section: Introductionmentioning
confidence: 94%
“…was not reduced when biochar was applied at a rate less than 2% and 0.5%, respectively [29]. Another study noted that, while nematode control was adequate in the specific system studied, biochar amendment could adversely impact pest control depending on the sorption strength of the particular type of biochar [10].…”
Section: Effects Of Biochar Amendment On Mitc Degradation and Adsorptionmentioning
confidence: 96%